IDENTIFYING FREQUENT SPELLING ERROR FOR YOUNG LEARNES OF PPA DELADA IO-126 HELEFANIKHA, GUNUNGSITOLI IDANOI (A PSYCHOLINGUISTICS STUDY) - Malili Zebua; Lefis Niwati Gulo; Yurman Ziliwu; Fitriana Purnamasari Laowo; Efen Ronalis Lase; Afore Tahir Harefa (Teaching English and Language Learning English Journal, 2026)
Spelling is an important component of English writing skills, especially for early learners. Repeated spelling errors not only indicate limited writing ability, but also reflect the cognitive processes involved in language acquisition and comprehension. This study aims to reanalyze the spelling errors of young learners at PPA Delada IO-126 Helefanikha, Gunungsitoli Idanoi, from a psycholinguistic perspective with a focus on orthographic knowledge. This study uses secondary data obtained from previous research on spelling errors. The data were analyzed by linking types of spelling errors, such as letter substitution, letter omission, and letter sequence errors, with the domains of language acquisition and language comprehension. The results showed that the dominant spelling errors were related to learners' weak orthographic knowledge, which indicated a negative relationship with their ability to acquire and comprehend written language. This study concludes that spelling errors are a representation of mental processes in language learning and have important implications for teaching English spelling to early learners.